The Design and Build a Children's Temperature Monitoring System Using The MLX90614 Temperature Sensor and NODEMCU ESP-12E Based On Android - Zidny Sholehan Abdullah (Journal of Engineering and Scientific Research, 2022)
The degree of children's health reflects the nation's health status, because children as the nation's next generation have abilities that can be developed in continuing the nation's development. The limited parental monitoring of children, so the authors make a child temperature monitoring device that can make it easier for parents to monitor their child's temperature in real time. This study uses a sensor temperature of the infrared MLX90614, NodeMCU ESP-12E as a controller programmed with the Arduino software idea later in the show via the LCD and the application blynk. This system was developed based on the needs of the children's monitoring system. The results of this research are that a child temperature monitoring system has been realized that can monitor the condition of a child's body in real time. Metode used isto compare data between Thermometer Gun with sensor systems ML X90614, then obtained an average difference of 0.0190 C and an average error of 0.053%. Keywords: Infrared sensor, MLX90614, real time, monitoring